“A Study On The Sustainable Investment Funds With Sepcial Reference To State Bank Of India Esg Mutual Fund Shcemes” - et.al, Dr. A. Anis Akthar Sulthana Banu (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Socially Responsible Investment (SRI) refers to the allocation of funds in certain practises that have a high social impact. It includes assessing businesses on the Environmental , Social and Governance (ESG) screens. A socially conscious investor may either invest directly in financial markets or through investment instruments such as mutual funds via ESG fund schemes. Very few of the numerous mutual fund organizations have implemented ESG Fund schemes to appeal to SRI investors. The SBI Mutual Fund is the first AMC to follow this and has been benchmarked against the Nifty 100 ESG indices. A correlation analysis is made among the results of the SBI Mutual Fund and the NIFTY to compare the four different types of SBI ESG funds and their sector wise participation in different industries. This research paper is methodological in nature as it interprets the published secondary data sources of the SBI Mutual Fund and the NIFTY indices. The goal of this paper is to assess the efficacy of the ESG Equity Fund in the investment portfolio of mutual fund investors and to enable small and medium-sized investors to contribute their money to ESG-driven mutual fund schemes.